Public reform paradoxes and the old effectiveness-efficiency problem - Pečarič, Mirko (2019)
Although effectiveness and efficiency are old comrades of public administrations, they still often cause unintended consequences. The relation between (absent) effectiveness and (overly emphasised) efficiency remains unresolved. The paper shows that effectiveness and efficiency are still used interchangeably, and despite the presence of negative effects, it comes as a surprise that important documentsstill address these terms without procedure or methodology to provide the content whereby they could be more clearly elaborated. Not only is the goal to achieve clearer meaning, but to accomplish results with the fewest possible negative effects. Alongside different management reforms, decision-makers must not lose sight of the whole; all reforms are only specific answers to inadequate previous ones, and it could be valuable to take a step back to see how/why different reforms emerge. The paper addresses the success/failure of reforms and the outcomes thereof. It claims the core problem of rational decision-making lies not in rationality per se, but in a lack of concept and/or insufficient attention to the behaviour of complex adaptive systems. With the help of complex adaptive systems, cybernetics, and combinations of effectiveness and efficiency, the paper presents the essential elements for adaptive (human) decision-making (such as diversity, variation, selection, adaptation, and integration) as the framework whereby unintended, reverse, and neutral effects can be reduced. New rules/decisions should be based on different levels of planning and adaptation, and on moving from the general to the more specific, in accordance with context specificity and unplanned, emergent things. It seems the hardest thing to address is the human character that does not (want to) recognise a situation as the situation in which some things must be spotted, evaluated, and changed if needed.
Pojmovi efektivnosti i efikasnosti već dugo su poznati javnoj upravi, no ipak često dovode do neplaniranih posljedica. Odnos između efektivnosti (koja izostaje) i efikasnosti (kojoj se pripisuje prevelika pažnja) ostaje neriješen. Ta se dva pojma i dalje upotrebljavaju kao istoznačnice, te s obzirom na negativne učinke čudi da se u važnim dokumentima i dalje navode bez procedure ili metodologije unutar kojih bi njihovo značenje bilo lakše pojasniti. Cilj nije isključivo pojasniti značenje, već ostvariti rezultate uz što manje negativnih učinaka. Kod provedbe reformi upravljanja donositelj odluka ne smije izgubiti širu sliku, a to je da su sve reforme specifični odgovori na neuspjele prošle reforme, te da korak unatrag može biti koristan i pokazati kako reforme nastaju. Rad se bavi (ne) uspjesima reformi i njihovim rezultatima. Autor drži da glavni problem racionalnog odlučivanja ne leži u samoj racionalnosti već u nedostatku koncepta i/ili u nedovoljnoj pažnji kada se radi o ponašanju kompleksnih adaptivnih sustava. Uz pomoć kompleksnih adaptivnih sustava, kibernetike i različitih kombinacija efektivnosti i efikasnosti u radu su predstavljeni temeljni elementi adaptivnog (kod ljudi) donošenja odluka (kao što su raznovrsnost, varijacija, selekcija, adaptacija i integracija). Oni čine okvir kojim se neplanirani, suprotni i neutralni učinci mogu ublažiti. Nova pravila i odluke treba zasnovati na različitim razinama planiranja i prilagodbe, te na pomaku od općenitog prema određenom, u skladu sa specifičnošću konteksta i neplaniranim pojavama u nastanku. Čini se da je pritom najteže uhvatiti se u ukoštac s ljudskom prirodom, koja ne prepoznaje (ili ne želi prepoznati) bilo koju situaciju kao onu u kojoj nešto treba zamijetiti, evaluirati i po potrebi provesti promjene.
Bilješke uz tekst.
Bibliografske bilješke uz tekst ; bibliografija: str. 523-527.
Summary ; Sažetak.
Keywords: Javna uprava -- Reforme -- Efektivnost -- Efikasnost